Strategi Nafkah Pada Rumah Tangga Pembudidaya Rumput Laut Desa Laikang Kecamatan Mangarabombang Kabupaten Takalar - Cahyani, Radhyta Putri Diah; Syarif, Asriyanti; Mudatsir, Rasdiana; Nailah, Nailah (Musamus University, 2024)
The research aims to analyze the livelihood strategy of seaweed cultivator households and the applicable livelihood system and to understand the management of livelihood assets. The research was conducted in Laikang Village, Mangarabombang District, Takalar Regency, from January to February 2024. Informants were determined using the Purposive Sampling method. Five households were taken from each hamlet to obtain a total of 30 households in the category of seaweed cultivators, running a seaweed business, and also diversifying their livelihoods. Qualitative descriptive is used to analyze the data. Research shows that the most dominant livelihood strategy used by seaweed cultivators is consolidation, characterized by a greater number of stretches compared to survival, having access to credit institutions, banks and other parties (collecting traders and the private sector). Meanwhile, the livelihood system is more of an on farm – on farm system due to supportive geographical conditions and the low level of knowledge and skills possessed by cultivators, so that people still depend on nature in trying or pursuing work that does not require high skills. Management of livelihood assets for seaweed cultivators involves five capitals, namely natural, human, social, financial and physical capital which is usually referred to as the asset pentagon.